MECHANICAL EQUIPMENT DESIGN OF COMPRESSION STATION FOR 255 KM NATURAL GAS TRANSMISSION PIPELINE - Putra Arrafian, Citra
The use of abundant natural gas in Indonesia requires a pipeline system to transmit the gas. The pipeline system in Java only connect East and Central Java. Related to this, Indonesian Ministry of Energy and Mineral Resource plans to build gas pipeline system from City A to City H to connect the disconnected areas from Central Java to West Java. Related to the construction of the pipeline system, a compressor station is also needed to increase the fluid pressure and separate the liquid phase fluid before it is transmitted to the pipeline. For this reason, it is necessary to design several mechanical equipments for the compressor station which include piping, separator and liquid tank, selection of pump and compressor-set, and also their placement layout in the stations. The design of mechanical equipments is carried out starting from the hydraulic analysis of the 255 km pipeline system, the selection of compressor and its driver, pressure vessels and piping system. The design is conducted based on the relevant codes such as ASME BPCV VIII Div. 1 for vessels and ASME B31.3: Process Piping for piping system. Based on the design that have been done, the design of separator and storage tank are obtained using SA-516 grade 70 whict has a thickness of 25 mm and 1 mm respectively, four 776 kW API 617 centrifugal compressors with its gas engine drivers. For the piping system, NPS 20 ERW API 5L X52 SCH 40 pipe is used which is as the pipe for the pipeline system. With the designed route and pipe support analyzed by AutoPIPE using ASME B31.3, the results show that the piping is safe with a maximum CSR of 0.96 due to gas pressure in the pipe after the compressor.